Avaliação da toxicidade de metais e pesticidas, isolados e em mistura, sobre duas espécies de oligochaeta nativos neotropicais - Gazonato Neto, Antonio José (Universidade Federal de São Carlos, 2018)
It is recognized the need of using native species as test organisms in toxicity studies in order to adequately reflect the typical properties of tropical systems and impacts as those of toxic or contaminating agents acting not only in isolation, but also in mixtures that depict the conditions found in ecosystems, this study aimed to test the suitability of two native species of invertebrates as test organisms in the determination of metals and pesticides toxicity. Acute and chronic toxicity tests were performed with the native species Dero furcatus and Allonais inaequalis (Oligochaeta, Naididae) under short and long term exposure to metals and pesticides with high frequency of occurrence in Brazilian aquatic systems. Among tested metals, cadmium, mercury and copper stand out for their high toxicity and wide use in industrial processes, as well as their high bioaccumulation power along the trophic chain. Even metals such as manganese, although with low toxicity, can cause long-term damage on aquatic biota, especially in mixtures with potential synergism. The pesticides carbofuran and diuron, compounds, widely used in Brazilian agricultural systems, were tested. The 96h LC50 of cadmium chloride was 627 μg L-1 and 364 μg L-1 for A. inaequalis and D. furcatus, respectively. For mercury chloride, 96h LC50 was 129 μg L-1 for A. inaequalis and 92 μg L-1 for D. furcatus. 96h LC50 for copper sulfate was 25.75 μg L-1 for A. inaequalis and 31.39 μg L-1 for D. furcatus. For manganese sulfate, 96h LC50 was 28155.16 μg L-1 for A. inaequalis and 18250.62 μg L-1 for D. furcatus. The sensitivity of the native species of oligochaetes was superior or similar to that of annelid species used worldwide as test organisms, such as Tubifex tubifex and Lumbriculus variegatus. This demonstrates the advantage of using native tropical species in toxicity assays. Chronic toxicity tests showed that even under very low and environmentally relevant sublethal concentrations, selected metals and pesticides negatively affected important aspects of the life cycle of oligochaetes, such as growth and survival, which in the long run could lead to a reduction in the natural population and consequent local extinction. Mixtures of metals have shown synergism, implying the probability of potentiation of toxic effects when metals occur together in the environment, demonstrating for example that although manganese alone does not present high toxicity, its concomitant natural occurrence and interaction with other metals may increase the toxic effects to greater levels than the simple addition of their isolated effects.
Keywords: Espécies nativas; Bentos; Metais tóxicos; Misturas; Pesticidas; Native species; Benthos; Toxic metals; Mixtures; Pesticides; CIENCIAS BIOLOGICAS::ECOLOGIA